Determinants of the effective tax rate in the tourism sector: a dynamic panel data model - José Moreno-Rojas; M. Rosario González-Rodríguez; Rosario Carmen Martín-Samper (Tourism & Management Studies)
This paper presents a dynamic model of the Effective Tax Rate (ETR) in the tourism sector. A dynamic model where the lagged endogenous variable ETR has been included as a regressor to identify the dynamic structure of the variable due to the existence of temporal adjustments between the short and long run in ETR payments has been estimated. The empirical analysis based on a panel data set over the 2008-2013 period explores the determinants of the ETR variable by using a Generalised Method of Moments (GMM) estimator controlling for heterogeneity in the tourism sector. The Arellano-Bond system GMM estimator has been used to estimate the model. The study seeks to shed light on the determinants of tax burden in the tourism sector covering the lack of studies on this topic. The findings obtained suggest that the ETR borne is determined by size, financing structure and type of entity. We deem the finding of the existence of non-linear relationships between ETR and size and financing structure relevant.